(untitled) (Journal of Economic Research & Business Administration, 2026)
This study examined the impact of government expenditure and inflation on Nigeria’s economic growth from 2000 to 2024 using the Autoregressive Distributed Lag (ARDL) model with structural breaks. Both short- and long-term relationships between government spending, inflation, and growth were analyzed using annual time-series data. Results indicate that government expenditure has a negative but statistically insignificant effect on economic growth in both periods, suggesting public spending has not significantly driven growth. Inflation shows a weak positive correlation, indicating minimal direct impact on growth. The model demonstrates strong explanatory power with R² values of 0.782 (long run) and 0.679 (short run). Significant F-statistics confirm the joint influence of variables on growth. A structural break was identified with a notable negative effect on economic growth, highlighting the adverse impact of major economic events or policy shifts. While long-run interaction effects between the structural break and explanatory variables are minor, short-run results reveal inflation’s positive and significant influence on growth. The error correction term is significant and negative, indicating a stable long-run equilibrium with 68.54% of short-run disequilibrium corrected per period. The findings suggest fiscal policy alone may not sustain long-term growth without efficient expenditure management, sound policy implementation, and macroeconomic stability. The study recommends improved allocation of public spending toward productive sectors, enhanced fiscal oversight, better policy coordination, and incorporating structural break considerations into economic planning and policymaking. Keywords: Fiscal рolicy, government expenditure, inflation, economic growth, structural break, ARDL Model, Nigeria.